Development or deterioration? work in rural Asia - Koppel, Bruce; Hawkins, John N.; James, William E. (Lynne Rienner Publishers, Inc., 1994)
This study concerns complex connections between macro and micro processes of employment diversification in rural Bangladesh, China, India, Indonesia, Malaysia, the Philippines and Thailand. It includes assessment of conditions where diversification does, and does not, appear to be "developmental."